2019
DOI: 10.1186/s13072-019-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Detailed insight into the dynamics of the initial phases of de novo RNA-directed DNA methylation in plant cells

Abstract: Background Methylation of cytosines is an evolutionarily conserved epigenetic mark that is essential for the control of chromatin activity in many taxa. It acts mainly repressively, causing transcriptional gene silencing. In plants, de novo DNA methylation is established mainly by RNA-directed DNA-methylation pathway. Even though the protein machinery involved is relatively well-described, the course of the initial phases remains covert. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…We also observed that the abundance of the 24-nt sRNAs that mapped to promoter regions was lower in infected plants in comparison to non-infected plants and transcription level of the genes mapped by these sRNAs was higher in Col-0 ecotype (when we compare infected versus mock inoculated plants). This finding is consistent with the knowledge that DNA methylation in regulatory regions inhibits transcription; therefore, a negative correlation between the amount of sRNAs (associated to a reduced level of methylation) and the level of mRNA is expected (Mette et al 2000;Přibylová et al 2019). On the other hand, controversy surrounds the effect of methylation of gene body regions.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed that the abundance of the 24-nt sRNAs that mapped to promoter regions was lower in infected plants in comparison to non-infected plants and transcription level of the genes mapped by these sRNAs was higher in Col-0 ecotype (when we compare infected versus mock inoculated plants). This finding is consistent with the knowledge that DNA methylation in regulatory regions inhibits transcription; therefore, a negative correlation between the amount of sRNAs (associated to a reduced level of methylation) and the level of mRNA is expected (Mette et al 2000;Přibylová et al 2019). On the other hand, controversy surrounds the effect of methylation of gene body regions.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the CHG context is the most affected one by DMV. Possibly, the cell reprogramming step [ 85 ] involving active [ 86 , 87 ] and passive [ 88 , 89 ] DNA demethylation followed by different mechanisms of de novo methylation (depending on sequence contexts) [ 90 , 91 ] and variations in the preferences towards methylation of specific cytosines compared to methylation density of some genomic regions [ 92 ] and correctness of pattern reestablishment due to (epi)genetic mechanisms [ 93 ] may be the most probable explanation both for the increased values of DMV and preferential demethylation of the CHG sequences.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported new insights into the speed by which an IR construct triggered TGS. By using an inducible IR construct, they observed targeted methylation and significant silencing of a reporter transgene just a few hours after the accumulation of IR‐derived siRNAs (Pribylova et al , 2019). Another recent study employed IR constructs to target methylation to distal enhancers of the flowering master regulator FLOWERING LOCUS T ( FT ) and trigger its down‐regulation (Zicola et al , 2019).…”
Section: Targeted Manipulation Of Dna Methylation In Plantsmentioning
confidence: 99%